2021
DOI: 10.1177/1756287221998134
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics in urology: the story so far and the road ahead

Abstract: Artificial intelligence (AI) has a proven record of application in the field of medicine and is used in various urological conditions such as oncology, urolithiasis, paediatric urology, urogynaecology, infertility and reconstruction. Data is the driving force of AI and the past decades have undoubtedly witnessed an upsurge in healthcare data. Urology is a specialty that has always been at the forefront of innovation and research and has rapidly embraced technologies to improve patient outcomes and experience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Several usability studies have been summarised in Table 2 based on their intended use. [52], [54] [55], [56] [57]- [59] [60]- [62] [63], [64] [65], [66] [67], [68] [69]- [72] [73]- [75] [76]- [78] [79], [80] [81], [82] [83], [84] To keep up with the tremendous growth in biomedical and healthcare papers, we've undertaken a comprehensive assessment of healthcare analytics across five subfields as illustrated in Table 3. Big data analytics is being used in the field of bioinformatics because to its complicated and enormous datasets, according to the results of the study.…”
Section: Big Data In Healthcarementioning
confidence: 99%
“…Several usability studies have been summarised in Table 2 based on their intended use. [52], [54] [55], [56] [57]- [59] [60]- [62] [63], [64] [65], [66] [67], [68] [69]- [72] [73]- [75] [76]- [78] [79], [80] [81], [82] [83], [84] To keep up with the tremendous growth in biomedical and healthcare papers, we've undertaken a comprehensive assessment of healthcare analytics across five subfields as illustrated in Table 3. Big data analytics is being used in the field of bioinformatics because to its complicated and enormous datasets, according to the results of the study.…”
Section: Big Data In Healthcarementioning
confidence: 99%
“…AI, big data and other technology applications in urology 28 . Adapted from Hameed BMZ, Dhavileswarapu AVLS, Naik N, et al .…”
Section: Figurementioning
confidence: 99%
“…A systematic review found that, in comparison with traditional clinical diagnosis and statistical outcome predictions, AI was found to be superior in 71.8% of studies 27 . In particular, AI and digital health are revolutionising the predictive prognosis, recurrence and survival outcomes for prostate cancer, reducing the risks of variability in observer‐dependent Gleason grading and improving reliability of biopsy specimen analysis 28 …”
Section: Digital Services and Urologymentioning
confidence: 99%
“…Students should be provided with courses focusing more on quantitative skills, incorporating machine learning and artificial intelligence, mathematical modeling, computation and simulation, and big data [25]. This is true both at the undergraduate and postgraduate level, with several medical specializations (like radiology, oncology, physical medicine, rehabilitation, rheumatology, cardiology, or urology, among others) expanding current knowledge levels, skills, and competencies [26,27]. Attempts to redesign specialist syllabus are very recent, but it can be anticipated that they will have a great impact on future medical practice.…”
Section: Integrating and Implementing Big Data Teaching Into The Medical Syllabus: Difficulties And Challengesmentioning
confidence: 99%